Energy Production Estimation and Data Monitoring System In 300 kWp Rooftop Solar Power Plant XYZ, Inc. - Geovani Rahmad Illahi; Irwan Iftadi; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
One of the greatest potential for renewable energy comes from solar energy. In Indonesia, the potential for solar energy can reach 3.294 GWP. This amount is very large when compared to other renewable energy production potentials. However, the problem with the solar power plant system is that the production of energy produced is influenced by time, weather, location, and the efficiency of the system can affect energy. This study discusses from the design process, estimation of energy production, and monitoring data on PV mini-grid. The calculation is done by estimation using PVsyst software. The monitoring system is made based on the specifications used. The design of this system is made to record data by measuring performance ratio and also calculating the efficiency of the system.